The Influence of Trust, Product Value and Beauty Influencers on Repurchase Interest in Halal Skincare Products - Nabila Tharrazana (Journal of Economics, Management, and Business, 2025)
The halalness of a product is a mandatory requirement for every consumer, especially Muslim consumers. Halal does not only include food or drinks, but halal cosmetics are also needed. Purpose - This study aims to analyze the effect of trust, product value and beauty influencers on the intention to repurchase halal skincare. Methodology - The method of data collection was done through a questionnaire. The population in this study were all consumers who bought halal skincare products. The sample required is 100 respondents using purposive sampling. This study uses multiple linear regression analysis techniques and data testing using the SPSS Statistics 25 program. Findings - The results of this study indicate that product trust and value have a positive and significant effect on the intention to repurchase halal skincare, while beauty influencers have a positive but not significant effect on the intention to repurchase halal skincare. The influence of the four variables is strong, this is indicated by the value of the coefficient of determination of 49%.